CORRUPTION CRIME THE VALUE OF DETERMINING ITS IMPLICATIONS IN THE DIFFERENTIATION (Journal of actual problems of jurisprudence, 2019)
In this article are considered value of an establishment of consequences of corruption crimes for their qualification